Cost-effectiveness of teduglutide in adult patients with short bowel syndrome: Markov modeling using traditional cost-effectiveness criteria. Issue 1 (30th October 2019) - Raghu, Vikram K; Binion, David G; Smith, Kenneth J
ABSTRACT: Background: Adults with short bowel syndrome have a high mortality and significant morbidity due to unsuccessful attempts at rehabilitation that necessitate chronic use of parenteral nutrition (PN). Teduglutide is a novel therapy that promotes intestinal adaptation to improve rehabilitation but with a price >$400, 000/y. Objective: The current study evaluated the cost-effectiveness of using teduglutide in US adult patients with short bowel syndrome. Methods: A Markov model evaluated the costs (in US dollars) and effectiveness (in quality-adjusted life years, or QALYs) of treatment compared with no teduglutide use, with a presumed starting age of 40 y. Parameters were obtained from published data or estimation. The primary effect modeled was the increased likelihood of reduced PN days per week when using teduglutide, leading to greater quality of life and lower PN costs. Sensitivity analyses were performed on all model parameters. Results: In the base scenario, teduglutide cost $949, 910/QALY gained. In 1-way sensitivity analyses, only reducing teduglutide cost decreased the cost/QALY gained to below the typical threshold of $100, 000/QALY gained. Specifically, teduglutide cost would need to be reduced by >65% for it to reach the threshold value. Probabilistic sensitivity analysis favored no teduglutide use in 80% of iterations at a $100, 000/QALY threshold. However, teduglutide therapy was cost-saving in 13% of model iterations. Conclusions: Teduglutide does not meet a traditional cost-effectiveness threshold as treatment for PN reduction in adult patients with short bowel syndrome compared with standard intestinal rehabilitation. Subpopulations that demonstrate maximum benefit could be cost-saving, and complete nonuse could lead to financial loss. Teduglutide becomes economically reasonable only if its cost is substantially reduced.